Fresh perspectives on major issues in pragmatics - Kirner-Ludwig, Monika, 1981- (London ; New York : Routledge, 2021)
This book showcases new and innovative developments and approaches in pragmatics, spotlighting perspectives from an international range of emerging scholars undertaking cutting-edge research pushing the field in new directions. The volume begins by taking stock of the most up-to-date developments in pragmatics research, as embodied by the work of a newer generation of pragmaticists. Chapters are organized around key areas of development within pragmatics, including intercultural and cross-cultural pragmatics, cognitive pragmatics, and new perspectives on referencing, implicating, and inferring, shedding further light on the ways in which pragmatics increasingly interfaces with other linguistic disciplines and on innovative methodologies. The book also places the focus on pragmatics approaches in languages other than than English, further expanding the borders of research. This book will be of particular interest to scholars in pragmatics interested in staying on top of the latest developments and future directions for the field.
OCLC-licensed vendor bibliographic record.
Keywords: Pragmatics; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics